One-pot synthesis and characterization of engineered hydrochar by hydrothermal carbonization of biomass with ZnCl2. (September 2020) - Li, Feiyue; Zimmerman, Andrew R.; Hu, Xin; Yu, Zebin; Huang, Jun; Gao, Bin
Abstract: Hydrochar, the product of hydrothermal carbonization of biomass, is a sustainable alternative to other carbonaceous environmental sorbents. However, its use has been limited due to its low surface area. A one-pot biomass/metal salt co-hydrothermal synthesis method might improve its sorptive properties while retaining its efficient production characteristic. Thus, bamboo sawdust and zinc chloride (ZnCl2 ) were combined in a hydrothermal reactor (200 °C, 7 h) for preparing modified hydrochar. Compared to the non-modified hydrochar, the hydrochar produced with the addition of ZnCl2 during hydrothermal treatment was more fully carbonized (C content increased from 54% to 64%), of higher surface area after acid washing (30 versus 1.7 m 2  g −1 ), and enriched in O-containing functional groups and of greater aromaticity (according to FTIR and XRD analysis). Because of these improved properties, Methylene blue adsorption capacity of the modified hydrochar increased by nearly 90% and by 257% after it was rinsed with acid. This study highlights the potential of this one-pot co-hydrothermal treatment of biomass in presence of metal salt to provide a simple and effective hydrochar with properties suitable for environmental remediation and water treatment. Graphical abstract: Image 1 Highlights: Co-hydrothermal treatment of biomass with ZnCl2 produced a novel hydrochar. Addition of ZnCl2 increased hydrochar specific surface areas and pore volume by 16 and 25 times, respectively. Addition of ZnCl2 during synthesis doubled hydrochar's methylene blue adsorption ability.